African Junta and Defence Spending: A Capture Effect or Self-preservation?. (9th December 2020) - Kodila-Tedika, Oasis; Khalifa, Sherif
Abstract: This paper examines the effect of the presence of a military ruler on military expenditure using a panel of sub-Saharan Africa countries. The paper also explores whether the relationship reflects a capture effect, is an outcome of the confrontational climate of the cold war or is a self-preservation effort by military rulers. The panel data estimations show that the presence of a military ruler has a statistically significant negative effect on military spending as a percentage of GDP. The coefficients are also not significantly different before or after the end of the cold war era. This implies that the negative relationship is driven by an effort by military rulers to preempt the ability of their peers to overthrow them from power. We also attempt to deal with potential endogeneity and consider the possibility of persistence in military spending. The paper uses the Arellano and Bond (1991) estimation technique that shows a negative but insignificant effect of the presence of a military ruler on military expenditure, while military spending shows a high degree of persistence.